Pertentangan yang Terjadi dalam Kasus Pemidanaan Hukuman Pidana Mati dan Hak Asasi Manusia di Indonesia - Mang Tra Himam Idayat (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The death penalty is one of the means of protecting society and the state in the form of prevention and action. Indonesia is one of the countries that still maintains and recognizes the legitimacy of the death penalty as a punishment for perpetrators of criminal acts. The death penalty is closely related to human rights because the death penalty is the most severe punishment because perpetrators of criminal acts will lose the right to life which is a priceless right. Therefore, there is a conflict between the imposition of the death penalty on perpetrators of criminal acts and human rights. This paper aims to determine the provisions regarding the death penalty and the protection of human rights. The type of research taken in this study is normative legal research that contains relevant issues. Normative legal research is research that is conducted by reviewing applicable laws and regulations or applying them to legal problems. Several laws and regulations in Indonesia still maintain the threat of the death penalty, although the death penalty has been criticized by human rights activists. Therefore, there is a compromise (criminal policy) in the Criminal Code, namely using the death penalty as an alternative punishment rather than the main punishment and only applies to very serious crimes.